Degradasi Limbah Cair Organik Industri Pulp Dan Kertas Menggunakan Peroxymonosulfate Yang Diaktivasi Oleh Katalis Α-Mn2O3@Α-MnO2-500 - Kristina Wijaya; Edi Saputra; Bahruddin Bahruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Water consumption is very high in industrial pulp and paper. In addition, water also ranked at third for the world wide used. Low COD ratio (0.3) and biodegradability around 0.5 in wasted is considered ideal. One of the alternative way which is Advanced Oxidation Process (AOP) able to degrade harmful organism who less active in the normal degradation process. Active radicals in AOP act produced as oxidizing agents to mineralize complex chemical substances in waste. One of the active radicals, which is sulfate radical (SO42-) has a high oxidation potential of 2.5 to 3.1 V. Several studies showed that radical sulfates can be produced by catalytic oxidation process, such as combination of Peroxymonosulfate with homogeneous metal ion catalyst (Fe2+, Mn2+, Ni2+, Co2+, Cd2+, Cu2+, Ag+1, Cr3+, Zn2+). In this study, AOP method Peroxymonosulfate which was activated with the catalyst α-Mn2O3@α-MnO2-500 were used to treat COD content in organic waste water from pulp and paper industry. The α-Mn2O3@α-MnO2-500 catalyst was produced from 1:3 molar potassium permanganate and maleic acid that calcined at 500 ºC. These catalysis were characterized by XRD, BET and FESEM. From the XRD analysis obtained a combined peak between α-MnO2 and α-Mn2O3 are comparable with JCPDS standard. From the FESEM analysis, the crystal size of the nanorod obtained is around 18-60 nm in width and 47-185 nm in length. In BET analysis, the surface area is 3.765 m2/g. The degradation of COD content, appear in 50ºC, at retention time of 240 minute, with concentrations of 0.4 g/L catalyst dose and 1.6 g/L Peroxymonosulfate (67,52%).Key word: AOP, COD, Peroxymonosulfate, Waste water, Catalyst